Implementation Of Tri Parārtha Teachings In The Life Of Hindus - Darma Laksana, Putu Buda; Wisarja, I Ketut; Asli, Luh; Nerta, I Wayan; Yunitha Asri Diantary Ni Made (Metta : Jurnal Ilmu Multidisiplin, 2023)
Tri Parārtha teachings consist of three parts, namely Asih, Punia, and Bhakti, which Hindus believe can lead to a prosperous and peaceful life. This study aimed to determine the implementation of Tri Parārtha teachings in the life of Hindus in Buleleng Customary Village. The method used was qualitative research with data analysis in the form of descriptive qualitative, namely data reduction, data presentation, and conclusion. The research results found that implementing Tri Parārtha teachings had positive implications for the life of Hindu communities in Buleleng Customary Village. These implications were not only felt by some people but have been felt by the entire Buleleng Customary Village community. Some of the implications included an increase in the attitude of asih (compassion), love, and a sense of togetherness reflected by the Hindu community to realize a prosperous life. As for the nature of giving or donations, such as giving in the form of goods (material) or energy (non-material) sincerely. In the form of devotional service (bhakti), it is not only devotion to God but also to others that will always create a harmonious life, such as no dispute between fellow Hindus. Also, there is an attitude of mutual greeting and close relations through togetherness between individuals and a group. Therefore, this attitude makes community life peaceful and avoids unwanted disputes.